Development of a Multicellular 3D Tumor Model to Study Cellular Heterogeneity and Plasticity in NSCLC Tumor Microenvironment - Arora, Leena; Kalia, Moyna; Dasgupta, Suman; Singh, Navneet; Verma, Anita K.; Pal, Durba (Frontiers in Oncology, 2022)
Tumor heterogeneity, results from cancer stemness, genetic and epigenetic changes, and cellular plasticity, is governed by a tumor microenvironment (TME) involving complex crosstalk between tumor cells and surrounding stroma. Studying tumor heterogeneity in 2D culture is challenging as it cannot stimulate the tumor microenvironmental features, such as hypoxia, nutrient unavailability, and cell-ECM interactions. We propose the development of multicellular (tri-culture) 3D spheroids using a modified hanging drop method in order to study the non-tumorigenic (BEAS-2B) vs. tumorigenic NSCLC cells (A549 /NCI-H460) interaction with lung fibroblasts (MRC-5) and monocytes (THP-1). Unlike non-tumorigenic model, the tumorigenic 3D spheroids demonstrated significant induction of cell proliferation, hypoxia, pluripotency markers, and a notable activation of fibroblasts as cancer-associated fibroblasts, and macrophages as tumor-associated macrophages, which was validated by zebrafish xenograft study and using human patient samples. Moreover, CD68+ macrophages isolated from tumorigenic spheroids exhibited profound induction of phenotypic and functional characteristics of the endothelial cell. In conclusion, our multicellular 3D biomimetic tumor model is a promising tool to study tumor-stroma interaction, cellular plasticity, and angiogenesis for targeting tumor heterogeneity and facilitate the chance of cancer therapy success against NSCLC.